(E)-4-[(4-Amino-5-bromopyridin-3-yl)iminomethyl]phenol - Cai, Mingjian (International Union of Crystallography, 2008)
In the molecule of the title compound, C(12)H(10)BrN(3)O, the pyridine and benzene rings are oriented at a dihedral angle of 34.93 (3)°. Intramolecular N—H⋯N and N—H⋯Br hydrogen bonds result in the formation of two non-planar five-membered rings. In the crystal structure, intermolecular O—H⋯N and N—H⋯O hydrogen bonds link the molecules to form a three-dimensional network.